Diversity of Saccharomyces cerevisiae Strains Isolated from Two Italian Wine-Producing Regions - Capece, Angela; Granchi, Lisa; Guerrini, Simona; Mangani, Silvia; Romaniello, Rossana; Vincenzini, Massimo; Romano, Patrizia (Frontiers in Microbiology, 2016)
Numerous studies, based on different molecular techniques analysing DNA polymorphism, have provided evidence that indigenous Saccharomyces cerevisiae populations display biogeographic patterns. Since the differentiated populations of S. cerevisiae seem to be responsible for the regional identity of wine, the aim of this work was to assess a possible relationship between the diversity and the geographical origin of indigenous S. cerevisiae isolates from two different Italian wine-producing regions (Tuscany and Basilicata). For this purpose, sixty-three isolates from Aglianico del Vulture grape must (main cultivar in the Basilicata region) and from Sangiovese grape must (main cultivar in the Tuscany region) were characterized genotypically, by mitochondrial DNA restriction analysis and MSP-PCR by using (GTG)5 primers, and phenotypically, by determining technological properties and metabolic compounds of oenological interest after alcoholic fermentation. All the S. cerevisiae isolates from each region were inoculated both in must obtained from Aglianico grape and in must obtained from Sangiovese grape to carry out fermentations at laboratory-scale. Numerical analysis of DNA patterns resulting from both molecular methods and principal component analysis of phenotypic data demonstrated a high diversity among the S. cerevisiae strains. Moreover, a correlation between genotypic and phenotypic groups and geographical origin of the strains was found, supporting the concept that there can be a microbial aspect to terroir. Therefore, exploring the diversity of indigenous S. cerevisiae strains can allow developing tailored strategies to select wine yeast strains better adapted to each viticultural area.